Improved re-ranking approach for multimedia search engines - Alqaraleh, Saed; Ramadan, Omar Salameh (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, a new re-ranking approach based on the multimedia contents and some user specific actions is presented for improving the performance of multimedia search engines. The proposed approach has the ability of working with all multimedia types: video, image, and audio. In addition, a group of descriptors with weight assigned dynamically have been used to describe the multimedia files accurately. Furthermore, the weight of each descriptor, which affects the file rank, is assigned based on the percentage of differences that found by the descriptor. Several experiments have been conducted and it has been observed that the proposed re-ranking approach shows the most relevant files to the top of the query results, and increases the percentage of the retrieved relevant files.
Keywords: implicit ranking; information retrieval; multimedia search engines; Re-ranking algorithm